Using M&E to Support Performance Based Planning and Budgeting in Indonesia - Ahern, Mark (World Bank, Washington, DC, 2014)
Since 2000, there has been growing interest in reforming Indonesia s budgeting systems to promote a more performance-orientated process. Indonesia is in the initial stages of this reform. A major challenge is determining the information needs of the central coordinating ministries. To date, these ministries have taken separate paths, developing their own monitoring and evaluation (M&E) systems, which are not linked to the planning and budgeting system, and creating new regulations and institutions to manage them. The result has been underused information and a high reporting burden at all levels. Furthermore, the current system places a greater emphasis on monitoring rather than evaluation. In 2011, representatives from the coordinating ministries participated in a series of high-level round table discussions to identify the steps needed to rationalize and coordinate M&E practices across institutions and to strengthen the links among data collection, evaluation, planning and budgeting. The round table process has confirmed that, while coordination is needed, establishing incentives for the demand and use of M&E information is critical to making the systems effective. This note identifies priority areas for future action building on this finding.